Acceleration Approximating Science and Technology Studies: On Judy Wajcman's Recent Oeuvre. (July 2019) - Vostal, Filip
This essay considers Judy Wajcman's book Pressed for Time: The Acceleration of Life in Digital Capitalism and an edited volume by her and Nigel Dodd entitled The Sociology of Speed: Digital, Organizational, and Social Temporalities . The essay claims that the two books challenge the one-dimensional and somewhat deterministic notion of a blanket, all-encompassing social acceleration dynamic, purportedly enveloping the whole of modernity, by offering new conceptual insights and empirical illustrations. Not only do the currently fashionable perspectives on acceleration in the social sciences overlook the nuances in temporal experience and the inextricable link between "fast" and "slow, " they also neglect the emerging temporal divisions inherent in the expansive nature of new information and communication technologies. Both books, in addressing such nuances and divisions, represent key landmarks in the sociology of time/speed and contribute significantly to the emerging social study of temporal transformation.